2021
DOI: 10.1097/upj.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Approaches to Battling Resident Burnout in a Urology Residency Program

Abstract: Introduction: Data suggest many U.S. physicians experience burnout, affecting up to 65% of U.S. urology resident physicians. We implemented a multifaceted Urology Resident Wellness Curriculum and measured its effect on burnout reported among our trainees.Methods: We created a 5-pronged Resident Wellness Curriculum: 1) faculty-sponsored Resident Wellness Fund, 2) social groups between 1 faculty and 2e3 trainees, 3) one-on-one structured mentorship, 4) resident-organized social outings using the Resident Wellnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…Burnout is often a hidden struggle or a concealed challenge because people may not recognize that they are experiencing it and may not feel comfortable speaking up about their symptoms. Burnout can build up slowly over time as people experience chronic stress, high levels of work demands, long hours, poor work-life balance, and lack of support from colleagues and supervisors [3,4] . People who are experiencing burnout may feel ashamed or embarrassed to admit it, thinking that it is a sign of weakness or a failure on their part.…”
Section: The Hidden Strugglementioning
confidence: 99%
See 1 more Smart Citation
“…Burnout is often a hidden struggle or a concealed challenge because people may not recognize that they are experiencing it and may not feel comfortable speaking up about their symptoms. Burnout can build up slowly over time as people experience chronic stress, high levels of work demands, long hours, poor work-life balance, and lack of support from colleagues and supervisors [3,4] . People who are experiencing burnout may feel ashamed or embarrassed to admit it, thinking that it is a sign of weakness or a failure on their part.…”
Section: The Hidden Strugglementioning
confidence: 99%
“…Anaissie et al [3] 2021 Innovative approaches to battling resident burnout in a urology residency program…”
Section: The Hidden Strugglementioning
confidence: 99%
“…Mentorship programs have also been described within urology residency programs themselves. Baylor College of Medicine created a 5-component resident wellness curriculum for their urology residency program that integrated structured mentorship, funding for social events, and wellness education [38]. They employed both dyad and group structures of mentorship in their program.…”
Section: Successful Mentorship Models In Urologymentioning
confidence: 99%
“…Numerous small studies have investigated a variety of interventions from access to a gym, to a program to strengthen coping mechanisms, to triannual faculty consultation to discuss goals, progress, and well-being, all of which were aimed at improving resident wellness [ 28 ]. A recent publication highlighted the benefit of a comprehensive wellness curriculum aimed at changing program culture [ 29 ]. This study found that over the 3 years studied, a formalized curriculum improved metrics of resident burnout, with the most meaningful intervention being resident-organized social outings.…”
Section: Opportunitiesmentioning
confidence: 99%